Problem-Based Learning in an online course of health education - Chagas, Isabel (2012)
The objectives of this project were to: i) describe the experience of implementing Problem-Based Learning in an online course over three consecutive academic years, ii) analyse the learning environment generated, iii) discuss impacts on students’ active participation, based on the analysis of their interactions. The participants were 30 students, working in five groups, and four tutors. All the interactions of each member of the five groups and their tutors in the discussion forums were identified and counted. The interactions identified were subjected to content analysis. The results showed a great variability in the degree of participation of each member of the group as well as the development of a group dynamic that did not appear to depend on the activity of each tutor. Moreover, in most groups, tutors reduced their participation during the semester. Regarding the ways students participated, and despite the individual variability observed, most students kept actively involved in the work contrarily to what research has shown about the uneven students’ participation in online courses. Two categories of interactions were identified in the groups according to the underlying objectives: learning-problem solving and group functioning. Whereas all groups were able to solve the problems under investigation, only a few demonstrated self-regulation capabilities leading to a great cohesion among the group members. The discussion of the results generated some guidelines for future investigations regarding the use of PBL in online environments.